A method for coupling analysis of association modules in product family design. (3rd June 2018) - Cheng, Xianfu; Xiao, Renbin; Wang, Haolun
ABSTRACT: For the coupling between modules in product family design, an approach to analysing coupled design for product family based on coupling incidence path and correlation impact degree is presented. The coupling of three cases is discussed, i.e. the coupling between platform modules, between platform module and customisation module, as well as between customisation modules. Then the interface among modules can be identified, and instigating components are considered as controllable factors and experimental design techniques are utilised to analyse their influence on the design objectives. According to analysis on coupling incidence path and correlation impact degree, the implementation sequence of modules is identified and corresponding decoupling strategies are proposed, if any, that may weaken the coupling of product family design. Finally, an example on the trolley design of gantry crane is provided to illustrate the proposed method for coupling analysis and decoupling of association modules in product family design.